2014
DOI: 10.1177/1557988314539501
|View full text |Cite
|
Sign up to set email alerts
|

Using the PRECEDE Planning Approach to Develop a Physical Activity Intervention for African American Men Who Visit Barbershops

Abstract: African American (AA) men have a higher prevalence of many chronic disease risk behaviors compared to Caucasian men, including physical inactivity. Innovative ways to reach AA men with interventions to increase physical activity (PA) and decrease other key risk factors are needed to reduce health disparities in this population. The barbershop is a natural but underutilized setting for reaching AA men. In the Fitness in the Shop (FITShop) study, shop owners, barbers, and customers were recruited from four local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…A variety of studies have demonstrated the feasibility of promoting African American men's health in barbershops, as it is a natural setting for African American men to congregate with similar others. Barbershop studies have focused on a variety of health topics for African American men, including physical activity (Hood et al 2015) and cardiovascular disease (Yancy 2011), and have also addressed the importance of prostate screening (Hill et al 2017), a highly stigmatized health topic among African American men. However, no known studies have sought to address the emotional support needs of African American men through barbershop-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have demonstrated the feasibility of promoting African American men's health in barbershops, as it is a natural setting for African American men to congregate with similar others. Barbershop studies have focused on a variety of health topics for African American men, including physical activity (Hood et al 2015) and cardiovascular disease (Yancy 2011), and have also addressed the importance of prostate screening (Hill et al 2017), a highly stigmatized health topic among African American men. However, no known studies have sought to address the emotional support needs of African American men through barbershop-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…These settings, which are accessible to all communities and are frequently visited, have offered important opportunities for both the reach and the reinforcement of health messages. 116,[184][185][186][187][188][189][190][191][192][193][194] Considering that ADDITION-Cambridge 111 and ADDITION-Denmark 112 , did not reveal any reduced all-cause, CVD-or T2DM-related mortality associated with an invitation to screening through the primary care centres, population-based screening for T2DM is the subject of debate. However, ADDITION used only a single mailed invitation, with no reminders to non-respondents and only the primary care centres as an outreach strategy.…”
Section: Implementation Of Screeningmentioning
confidence: 99%
“…On average, the value of the financial workshops was rated 9.8 (range = 9.0-10.0) by attendees. A detailed description of the FITShop study intervention and control components is presented in Hood et al (2015).…”
Section: Methodsmentioning
confidence: 99%